The Effect Of System Quality And User Confidence In Sharia E-Wallets On Non-Cash Transaction Decisions - Siti Kurniawati; Ahadiah Agustina; Zaenafi Ariani (JPS (Jurnal Perbankan Syariah), 2026)
Purpose- This study aims to examine how the quality of digital services and user confidence levels influence decisions to use sharia-based non-cash payments. The urgency of this study arises from the increasing need for transaction instruments that are not only efficient, but also trusted to be secure and in accordance with sharia principles. Method- In terms of methodology, this study uses a quantitative approach through a survey of 102 active users in the West Nusa Tenggara region. The data collection instrument was a Likert scale questionnaire, which was then processed using multiple linear regression analysis through the JASP application. Findings- The findings show that both independent variables have a positive and significant influence on the decision to transact digitally, with a model contribution of R² = 0.723. The trust factor is recorded as the strongest determinant, as indicated by the largest coefficient value (β = 0.550; p < 0.001). Based on these results, the study concluded that system quality and confidence in security and sharia compliance are important factors in encouraging the use of modern payment services. Implication- The implication is that service providers need to strengthen technological stability, increase transparency, and build credibility so that the adoption of sharia digital transactions can develop more widely.